The impact of HIV and AIDS on the world of work: global estimates (Geneva, 2018)
"The majority of people living with or affected by HIV and AIDS are of working age. It is essential to understand and measure the economic and social impacts of the epidemic on the labour force. Bringing together health data, in particular HIV prevalence data, with labour force, economic and demographic data, the report sets out social and economic impacts on workers and their households for 2005, 2010 and 2015, as well as projections for 2020. The report provides snapshots at five-year intervals of HIV prevalence, deaths, and full and partial inability to work for the male and female labour force by country, for various groups of countries and globally. It also gives estimates for other key economic and social impacts (lost earnings, additional care work, child labour and impact on children’s education). Acknowledging that anti-retroviral therapy is keeping workers healthy and productive, and recommending the scaling-up of treatment, the report stresses the need to better integrate health data with social and economic data to capture all dimensions of multifaceted AIDS-related diseases. This report aims at providing ILO constituents and other stakeholders with quantitative data to inform national HIV and AIDS policy and programmes in the world of work."